Divergence in the Regulation of the Salt Tolerant Response Between Arabidopsis thaliana and Its Halophytic Relative Eutrema salsugineum by mRNA Alternative Polyadenylation - Ma, Hui; Cai, Lingling; Lin, Juncheng; Zhou, Kaiyue; Li, Qingshun Q. (Frontiers in Plant Science, 2022)
Salt tolerance is an important mechanism by which plants can adapt to a saline environment. To understand the process of salt tolerance, we performed global analyses of mRNA alternative polyadenylation (APA), an important regulatory mechanism during eukaryotic gene expression, in Arabidopsis thaliana and its halophytic relative Eutrema salsugineum with regards to their responses to salt stress. Analyses showed that while APA occurs commonly in both Arabidopsis and Eutrema, Eutrema possesses fewer APA genes than Arabidopsis (47% vs 54%). However, the proportion of APA genes was significantly increased in Arabidopsis under salt stress but not in Eutrema. This indicated that Arabidopsis is more sensitive to salt stress and that Eutrema exhibits an innate response to such conditions. Both species utilized distal poly(A) sites under salt stress; however, only eight genes were found to overlap when their 3' untranslated region (UTR) lengthen genes were compared, thus revealing their distinct responses to salt stress. In Arabidopsis, genes that use distal poly(A) sites were enriched in response to salt stress. However, in Eutrema, the use of poly(A) sites was less affected and fewer genes were enriched. The transcripts with up-regulated poly(A) sites in Arabidopsis showed enriched pathways in plant hormone signal transduction, starch and sucrose metabolism, and fatty acid elongation; in Eutrema, biosynthetic pathways (stilbenoid, diarylheptanoid and gingerol) and metabolic pathways (arginine and proline) showed enrichment. APA was associated with 42% and 29% of the differentially expressed genes (DE genes) in Arabidopsis and Eutrema experiencing salt stress, respectively. Salt specific poly(A) sites and salt-inducible APA events were identified in both species; notably, some salt tolerance-related genes and transcription factor genes exhibited differential APA patterns, such as CIPK21 and LEA4-5. Our results suggest that adapted species exhibit more orderly response at the RNA maturation step under salt stress, while more salt-specific poly(A) sites were activated in Arabidopsis to cope with salinity conditions. Collectively, our findings not only highlight the importance of APA in the regulation of gene expression in response to salt stress, but also provide a new perspective on how salt-sensitive and salt-tolerant species perform differently under stress conditions through transcriptome diversity.